الدعم الديبلوماسي السوري للثورة الجزائرية - لميش الصالح (My University, 2013)
الملخص Syrian diplomatic support for the Algerian revolution The Syrian position on the Algerian revolution was not limited to official and popular support only, but rather to diplomatic support in all the conferences and forums that were held at the African, Arab or international levels